Peningkatan Hasil Produksi Biogas Melalui Penggunaan Bahan Tambahan Seperti Nitrogen (N), Fosfor (P), Dan Kalium (K) Dalam Pengolahan Sampah Domestik - Dewi Murniati (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Waste management poses an inevitable challenge in human life and is often poorly handled. One type of waste causing significant issues is solid organic waste from households, which can lead to unpleasant odors and soil and water pollution due to its high organic content. However, the potential of organic waste to be converted into biogas, as an alternative energy source, can be harnessed through anaerobic processes. In this experiment, the researchers aimed to observe the effectiveness of adding additives to organic waste with varying doses. The organic content in the substrate for anaerobic microbes was represented by VS (volatile solid), with the inoculum sourced from cow dung. The experiment results indicate that adding NPK fertilizer additives with different doses increases biogas production. This suggests that the use of NPK additive can enhance the efficiency of anaerobic processes in generating biogas from organic waste.